2009
DOI: 10.3171/2009.3.spine08724
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical surgery for the treatment of cervical degenerative myelopathy

Abstract: Object The objective of this systematic review was to use evidence-based medicine to examine the efficacy of anterior cervical surgery for the treatment of cervical spondylotic myelopathy (CSM). Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and key words relevant to anterior cervical surgery and CSM. Abstracts were reviewed, and studies meeting inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…[33] The Joint Guidelines Committee of the American Association of Neurological Surgeons/Congress of Neurological Surgeons found that surgery for CSM leads to signifi cant improvement that is maintained for a minimum of 5 years to as long as 15 years postoperatively. [34] Another recent study has shown that surgery for CSM is associated with signifi cant functional recovery and such recovery reaches a plateau at six months after surgery. [35] However, approximately, 4% of patients show neurological deterioration after decompressive surgery.…”
Section: Prognosis Of Surgery For Cervical Spondylotic Myelopathymentioning
confidence: 99%
“…[33] The Joint Guidelines Committee of the American Association of Neurological Surgeons/Congress of Neurological Surgeons found that surgery for CSM leads to signifi cant improvement that is maintained for a minimum of 5 years to as long as 15 years postoperatively. [34] Another recent study has shown that surgery for CSM is associated with signifi cant functional recovery and such recovery reaches a plateau at six months after surgery. [35] However, approximately, 4% of patients show neurological deterioration after decompressive surgery.…”
Section: Prognosis Of Surgery For Cervical Spondylotic Myelopathymentioning
confidence: 99%
“…Therefore, some surgeons would suggest early surgery for patients with CSM to ameliorate the risk of SCI. 2,9,19,21,22,24,27,33 However, there are insufficient data to correlate CSM with SCI, and whether the risk of SCI can be altered by surgical intervention remains elusive.…”
mentioning
confidence: 99%
“…Anterior cervical corpectomy and fusion (ACCF) is ideally suited in cases where the compressive pathology is not confined to the disc space region, and extends behind the vertebral body [56,29,34].…”
Section: Anterior Cervical Corpectomy and Fusionmentioning
confidence: 99%